Skala Pengukuran Burnout Mahasiswa Dalam Penyelesaian Skripsi: Instrumen Pendukung Pengembangan “BAPER” - Setyaputri, Nora Yuniar; Khususiyah, Khususiyah; Ayuningtyas, Putri (Universitas Nusantara PGRI Kediri, 2022)
This research stems from the rise of the burnout phenomenon experienced by students when completing their thesis. The burnout that makes the study period will have a negative impact on the student's motivation to learn and self-esteem, as well as on the assessment of the accreditation program. Students in these cases often vent their emotions on social media such as writing statuses on WhatsApp, Facebook, and Instagram. Their expressive writings are considered unethical. Therefore, research was conducted with the aim of developing a Handbook for Expressive Writing (BAPER) which could be tested both theoretically and practically. The research method used is Research and Development from Borg & Gall. Currently, the research stage is entering the third stage, namely the Development of Initial Product Drafts, one of which is the preparation of instruments. Instrument validity and reliability are important things that must be considered to obtain representative data for the purposes of selecting research samples that will use purposive sampling. The instruments were tested on 37 undergraduate students who were in the process of completing their thesis. They are scattered in several study programs in the Nusantara PGRI Kediri. Then obtained 14 valid items with a reliability index of 0.886. Items that have been valid and reliable can represent all indicators of burnout. Based on these results, the Student Burnout Measurement Scale can be used as a measuring tool in the next research stage.